Plantas de cobertura, cultivares e nematicidas no manejo de meloidogyne javanica e pratylenchus brachyurus em soja - Dalla Favera, Diego (2014)
The root-knot nematode Meloidogyne javanica is a major plant parasitic nematode of soybean. Its control should be based on the use of all available methods. Thus the objective of the study was to evaluate the effect of different cover crops and nematicides in the management of M. javanica in soybean, besides the reaction of soybean cultivars and cover crops to plant parasitic nematode. The field study was conducted in Julio de Castilhos / RS, in the season 2013/2014. The treatments consisted of a factorial with different cover crops in winter and different nematicides in soybeans. The population of M. javanica in the soil and roots and soybean yield was evaluated. In growth chamber was evaluated the reaction of 45 soybean cultivars and cover crops to M. javanica. Assays were carried out in pots of 700 cm3 and were inoculated with 5000 juveniles and eggs of M. javanica in each pot. At 60 days after inoculation was performed to evaluate the gall index, fresh weight of root and population of M. javanica in the soil and roots (juveniles and eggs). From these values were calculated nematode density and the reproduction factor. Cover crops and nematicides showed significant effects on the control of M. javanica and soybean yield. All 45 cultivars are presented susceptible to M. javanica. Already cover crops were resistant to plant parasitic nematode.